Some Initial Observations on a Building Excavated on Fabrika in Nea Paphos in Cyprus by the Australian Archaeological Mission - Craig Barker (Ksiegarnia Akademicka Publishing, 2015)
The Australian archaeological mission to Nea Paphos in Cyprus has begun exploring the remains of a structure to the rear of the cavea of the ancient theatre on the southeastern edge of the hill known as Fabrika. The preliminary results of this excavation suggest a significantly large post-medieval building constructed using stone taken from the former theatre. The building appears to have been used in some sort of industrial production, the precise nature of which is not yet determined, and is perhaps the source of the etymology of the name of the hill. This paper discusses a need for a reassessment of this area of the city of Nea Paphos in its more recent history, and discusses the needs for a better understanding of the urban relationship between Fabrika and the theatrical precinct during the Hellenistic and Roman periods.